Is there a relationship between pain and psychological concerns related to falling in community dwelling older adults? A systematic review. (November 2014) - Stubbs, Brendon; West, Elizabeth; Patchay, Sandhi; Schofield, Pat
Abstract Purpose: To systematically review and synthesise the research evidence linking pain to psychological concerns about falling in community dwelling older adults. Methods: A systematic review was conducted in accordance with the preferred reporting items of systematic reviews and meta-analysis statement (PRISMA). Major electronic databases were searched from inception until June 2013. Two authors independently conducted the searches, extracted data and completed methodological quality assessments. Articles were included if they measured one of the psychological concerns related to falling in a sample of community dwelling older adults with pain, or explored the association between the two. Results: Of a potential 892 articles, 12 met the eligibility criteria (n = 3398). The methodological quality of the included studies was variable and none of the included studies primary aim was to investigate the relationship between pain and psychological concerns related to falls. Two studies found significant differences in psychological concerns related to falls in older adults with pain and a control group. Nine out of 10 studies reported a significant correlation between pain and psychological concerns related to falls in their sample. Conclusion: This review provides provisional evidence that pain is associated with fear of falling (FOF), avoidance of activities due to FOF and falls efficacy in community dwelling older adults. Implications for Rehabilitation Pain is a common and pervasive problem in community dwelling older adults and can affect an individual's mobility, levels of physical activity and increase their falls risk. Psychological concerns related to falls, such as fear of falling (FOF), falls efficacy and balance confidence are also common and troublesome issues in older adults, yet the association with pain has not been investigated with a systematic review. This review provides provisional evidence that pain may increase older adult's risk of developing FOF, avoiding activities due to a FOF and impact their falls efficacy. In recognition of the findings of this review, clinicians working with older adults with pain should consider assessing psychological concerns related to falls and if necessary intervene if they identify an individual at risk.